تقييم فعالية نظم معلومات الموارد البشرية المستخدمة في جامعة تشرين دراسة ميدانية - غدير, باسم; عيسى, جميل (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed to evaluate the effectiveness of human resources information system (HRIS) in Teshreen university, by studying the three dimensions, which (HRIS) based upon it: the information quality, User Satisfaction and system security. The researcher tested his Hypotheses by using T test for one sample, for analysis data that collected by Questionnaire that has distributed to /55/ employees in the university how work in HR. The value of Cronbach's alpha = /0.843/, and The main finding of the research can be summarized there is reduced effectiveness of HRIS, because of low level of the quality of information, the low of User Satisfaction average, and the weakness of HRIS security level in Teshreen university. هدف الباحث من خلال هذه الدراسة إلى تقييم مدى فعالية نظم معلومات الموارد البشرية المستخدمة في جامعة تشرين، من خال الاستناد إلى تقييم ثلاث أبعاد رئيسة تبنى عليها فعالية نظم المعلومات وهي: جودة المعلومات، رضا المستخدم، وحماية النظم. قام الباحث باختبار فرضياته من خلال تحليل البيانات الأولية التي تم جمعها عن طريق استبانة، تم توزيعها على عينة ميسرة من العاملين في مجال الموارد البشرية بلغت 55 مفردة، تجاوزت قيمة معامل ألفا كرونباخ /0.843/، وتوصلت الدراسة إلى انخفاض فعالية نظم معلومات الموارد البشرية المستخدمة في جامعة تشرين، حيث أظهرت آراء العينة ميلاً إلى عدم الرضا عن كل من جودة المعلومات الناتجة عن هذه النظم، مترافقا مع انخفاض في درجة الرضا عن استخدام هذه النظم، وعدم القبول بمستوى الحماية المرافق لها. حيث استخدم الباحث في تحليله الاحصائي اختبار T ستيودينت لعينة واحدة بمساعدة برنامج spssالاحصائي بالإصدار /20/